ORKESTRASI TATA KELOLA KECERDASAN ARTIFISIAL (AI) DI SEKTOR PUBLIK INDONESIA - Dionisius Salvavictori Wanggur; Irfan Dwiguna Sumitra (Universitas Komputer Indonesia, 2026)
The integration of Artificial Intelligence (AI) in the public sector offers the potential for bureaucratic efficiency aligned with the vision of Golden Indonesia 2045. However, there is a significant orchestration gap between national strategic ambitions and the reality of currently available policy instruments. This study aims to analyze the challenges of AI governance in Indonesia, specifically highlighting the urgency of transitioning from voluntary approaches (soft law) to binding regulations (hard law). This study employs a qualitative approach with the Document Analysis method to dissect key policy instruments, namely the National Strategy for Artificial Intelligence (Stranas KA) and the Minister of Communication and Informatics Circular Letter No. 9 of 2023. The data analysis technique refers to the interactive model by Miles, Huberman, and Saldaña. The results indicate that Indonesia's current regulatory framework is still dominated by ethical appeals without strict sanctions. This creates a legal vacuum that poses risks to public decision accountability and data protection. This study concludes the need for specific regulation at the statutory level to ensure legal certainty and public trust. Keywords: Artificial Intelligence; Public Sector Governance; Public Policy; AI Ethics; Digital Transformation.